2017
DOI: 10.4103/0976-3147.203852
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Utilization of Physiotherapy Service among Children with Cerebral Palsy in Jalandhar District of Punjab

Abstract: Background:Physiotherapy plays a central role in the management of children with cerebral palsy (CP); however, literature describing the use of physiotherapy service and the factors affecting utilization of physiotherapy service for this group of children in the Indian context remain unexplored.Aims and Objectives:To describe the utilization of physiotherapy services and explore the factors affecting utilization of physiotherapy services among children with CP of Jalandhar district of Punjab.Methodology:During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Study by Sinha and Sharma found that advice for rehabilitation by treating primary physician is an important influencer for service utilization and a poor referral system, not fully utilizing expertise available within system, adversely affects it. [ 3 ] Previous studies done by Kaminker et al . and Chiarello et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Study by Sinha and Sharma found that advice for rehabilitation by treating primary physician is an important influencer for service utilization and a poor referral system, not fully utilizing expertise available within system, adversely affects it. [ 3 ] Previous studies done by Kaminker et al . and Chiarello et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mentioned environmental factors including transportation and area of residence as one of the significant barriers for rehab utilization, though none of them have specifically looked at distance as a measure. [ 3 7 16 ] Studies in South African areas have found distance as one of the prime reasons for nonutilization in disabled. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations